Pomegranate Juice Prevents the Formation of Lung Nodules Secondary to Chronic Cigarette Smoke Exposure in an Animal Model. (30th November 2017) - Husari, Ahmad; Hashem, Yasmine; Zaatari, Ghazi; El Sabban, Marwan
Abstract : Background . Cigarette smoke (CS) induces an oxidative stress, DNA damage, and lung cancer. Pomegranate juice (PJ) possess potent antioxidant activity attributed to its polyphenols. We investigated whether PJ supplementation would prevent the formation of lung nodules, attenuate mitotic activity, and reduce hypoxia-inducible factor-1 α (HIF-1 α ) expression secondary to CS exposure in an animal model. Methods . Mice were divided into: Control group, CS group, CS + PJ group, and PJ-only group. CS and CS + PJ were exposed to CS, 5 days per week, for a total of 5 months. Animals were then housed for additional four months. CS + PJ and PJ groups received PJ throughout the experiment period while others received placebo. At the end of the experiment, the incidence of lung nodules was assessed by (1) histological analysis, (2) mitotic activity [measurement of PHH3 antibodies], and (3) measurement of HIF-1 α expression. Results . The incidence of lung nodules was significantly increased in CS. CS exposure significantly increased PHH3 and HIF-1 α expression. PJ supplementation attenuated the formation of lung nodules and reduced PHH3 and HIF-1 α expression. Conclusion . PJ supplementation significantly decreased the incidence of lung cancer, secondary to CS, prevented the formation of lung nodules, and reduced mitotic activity and HIF-1 α expression in an animal model.